PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI SOSIAL PADA MATA PELAJARAN IPS SEKOLAH DASAR - Mochamad Irsan Setiadi; Hafiziani Eka Putri; Ade Hidayat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to enhance students' social literacy skills in the Social Studies subject at 076 Sukajadi Elementary School, Bandung City, West Java, through the implementation of the Problem Based Learning (PBL) model. The research method used in this study was Classroom Action Research (CAR) with the spiral model of Kemmis-McTaggart. The subjects of this study were 30 fifth-grade students, comprising 13 males and 17 females. Data were collected using observation sheets and learning outcome tests. The results of the study indicate that students' social literacy skills in the Social Studies subject at 076 Sukajadi Elementary School can be improved through the use of the Problem Based Learning model in teaching and learning. It is hoped that the findings of this study will assist teachers in selecting the appropriate instructional model to enhance students' social literacy skills, particularly in aspects such as improving intellectual abilities, cooperation, attitudes, and social values.